1988
DOI: 10.1021/j100313a003
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced electron transfer from colloidal cadmium sulfide to methylviologen: a picosecond transient absorption study

Abstract: 255complex so much increases the density of rovibronic levels that all resolution of AlO-based vibrational level structure is lost in excited-state complex formation.I0 ConclusionThe results obtained thus far indicate that using an extrapolation of the techniques we have outlined here, it will be possible to (1) evaluate nontransition-metal M(C0)2 (x = 1,2) binding energies, (2) study long-lived metal oxide-carbon dioxide solvation complexes formed in metal-C02 complex oxidation, and (3) characterize the spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…A multiexponential decay unsurprisingly indicates several processes at play in the complex M. thermoacetica-CdS hybrids. Rapid picosecond decays were previously measured with colloidal CdS that featured molecular acceptors with fast e − transfer behavior (24)(25)(26). As hot e − relaxation in Cd-chalcogenide quantum dots occurs in the subpicosecond regime, this process does not likely contribute to the TA kinetics in the measured time scale (27).…”
Section: −1mentioning
confidence: 97%
“…A multiexponential decay unsurprisingly indicates several processes at play in the complex M. thermoacetica-CdS hybrids. Rapid picosecond decays were previously measured with colloidal CdS that featured molecular acceptors with fast e − transfer behavior (24)(25)(26). As hot e − relaxation in Cd-chalcogenide quantum dots occurs in the subpicosecond regime, this process does not likely contribute to the TA kinetics in the measured time scale (27).…”
Section: −1mentioning
confidence: 97%
“…The time-resolved transient absorption spectra of semiconductor particles have also been investigated by a fast kinetic spectroscopy to clarify their primary photo-chemical events [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…31 Investigations of CdS NPs with methyl viologen cations as adsorbates (CdS-MV 2+ ) showed that MV 2+ is able to accept the photoexcited electron from the CdS NPs. 7,[32][33][34][35] Recently, the fem-tosecond dynamics of the charge carriers were studied and it was revealed that electron transfer takes place in 200-300 fs. 36 In the present work, we report on the femtosecond charge carrier dynamics of CdSe NP-quinone composites.…”
Section: Introductionmentioning
confidence: 99%